2020
DOI: 10.1038/s41436-019-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of comorbid conditions among women who carry an FMR1 premutation

Abstract: Purpose Emerging evidence indicates that women who carry an FMR1 premutation can experience complex health profiles beyond the two well-established premutation-associated disorders: fragile X–associated primary ovarian insufficiency (FXPOI, affects ~20–30% carriers) and fragile X–associated tremor–ataxia syndrome (FXTAS, affects ~6–15% carriers). Methods To better understand premutation-associated health profiles, we collected self-reported medical histories on 355 carrier women. Results Twenty-two health co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
5
35
1
Order By: Relevance
“…However, the effect of the PM alleles may extend beyond those two definitive disorders, FXTAS and FXPOI, especially in the female carriers, where other physical changes, such as autoimmune thyroid disease and other immune-related disorders, as well as psychiatric problems including social phobia, hostility, obsessive/compulsive behavior, and anxiety/depression can be seen; in addition, common disorders such as fibromyalgia, hypertension and migraines have been reported to be more common in female carriers that in the general population (Coffey et al, 2008 ; Soontarapornchai et al, 2008 ; Bourgeois et al, 2009 , 2011 ; Roberts et al, 2009 ; Leehey et al, 2011 ; Loesch and Hagerman, 2011 ; Seltzer et al, 2012 ; Winarni et al, 2012 ; Au et al, 2013 ; Wheeler et al, 2014 ). However, most of the data obtained by comparing samples of carriers with non-carriers have yielded inconsistent results, in part attributable to selection bias (Hunter et al, 2008 ; Allen et al, 2020 ), and thus provide limited insight into the effects of PM alleles on female phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the PM alleles may extend beyond those two definitive disorders, FXTAS and FXPOI, especially in the female carriers, where other physical changes, such as autoimmune thyroid disease and other immune-related disorders, as well as psychiatric problems including social phobia, hostility, obsessive/compulsive behavior, and anxiety/depression can be seen; in addition, common disorders such as fibromyalgia, hypertension and migraines have been reported to be more common in female carriers that in the general population (Coffey et al, 2008 ; Soontarapornchai et al, 2008 ; Bourgeois et al, 2009 , 2011 ; Roberts et al, 2009 ; Leehey et al, 2011 ; Loesch and Hagerman, 2011 ; Seltzer et al, 2012 ; Winarni et al, 2012 ; Au et al, 2013 ; Wheeler et al, 2014 ). However, most of the data obtained by comparing samples of carriers with non-carriers have yielded inconsistent results, in part attributable to selection bias (Hunter et al, 2008 ; Allen et al, 2020 ), and thus provide limited insight into the effects of PM alleles on female phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Women with alleles between 35-44 CGG repeats seem to present diminished ovarian function but regular menses and occult primary ovarian insufficiency (Streuli et al, 2009;Karimov et al, 2011;Pastore et al, 2012); however, other studies found no association between FMR1 intermediate alleles and POI (Bennett et al, 2010;Murray et al, 2014;Voorhuis et al, 2014). Other medical and psychological issues reported in females are hypothyroidism, hypertension, endocrine dysfunctions, chronic pain, fibromyalgia, autoimmune diseases, neuropathies, migraines, dementia, and psychiatric conditions, such as anxiety and depression (Allen et al, 2007(Allen et al, , 2020Bailey et al, 2008;Hunter et al, 2010;Winarni et al, 2012;Wheeler et al, 2014a,b;Lozano et al, 2016;Movaghar et al, 2019). Collectively included under the term FXAND [fragile Xassociated neuropsychiatric disorders; (Hagerman et al, 2018)], such emotional and neuropsychiatric disorders, have been shown to be more common in female carriers compared to noncarriers.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively included under the term FXAND [fragile Xassociated neuropsychiatric disorders; (Hagerman et al, 2018)], such emotional and neuropsychiatric disorders, have been shown to be more common in female carriers compared to noncarriers. In a recent work by Dr. S. Sherman's group, which investigated the association between the PM diagnosis and CGG repeat expansion in female carriers, the most common symptoms reported were anxiety and depression, migraine, headaches, and sleep problems (Allen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is known that there is a brain-blood difference in FMR1 mRNA expression, and potentially of the CGG expansion [14,[77][78][79]. Similar concerns apply to the activation ratio (AR), which did not show any relation to any of the cognitive or other phenotypic test scores in the recent comprehensive study [37]. Our analysis of this relationship in a small subsample using activation ratio based on the intensity of the appropriate bands on Southern blots [59], also showed an extensive variation between individuals without any correspondence to individual phenotypes and, for this reason, activation ratio was not considered as a potential confounder in correlation analysis.…”
Section: Discussionmentioning
confidence: 96%
“…These results suggested that there may be a slow subclinical decline in executive functioning and/or degradation of motor functioning, combined with (and perhaps augmented by) stress and diminished adaptive capacity, in apparently asymptomatic premutation females. However, most of the results that have been obtained by comparing samples of carriers with non-carriers have yielded inconsistent results, in part attributable to selection bias [36,37], and thus provide limited insight into the effects of premutation alleles on female phenotypes. Likewise, the results of correlations between phenotypic (especially neuropsychiatric) findings and fragile X genotype, including CGG repeat size, FMR1mRNA levels and the FMR1 activation ratio, have been inconsistent [38], so that the issue of the dynamics of brain changes associated with PM alleles other than the recognised FXTAS manifestations still remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%